Sublethal Endpoints in Non-target Organism Testing for Insect-Active GE Crops - Roberts, Andrew; Boeckman, Chad J.; Mühl, Marina; Romeis, Jörg; Teem, John L.; Valicente, Fernando H.; Brown, Judith K.; Edwards, Martin G.; Levine, Steven L.; Melnick, Rachel L.; Rodrigues, Thais B.; Vélez, Ana M.; et al. (Frontiers in Bioengineering and Biotechnology, 2020)
Historically, genetically engineered (GE) plants that have incorporated genes conferring insect protection have primarily used Cry proteins derived from Bacillus thuringiensis (Bt) to achieve their insecticidal phenotype. As a result, regulators have developed a level of familiarity and confidence in reviewing plants incorporating these insecticidal proteins. However, new technologies have been developed that produce GE plants that incorporate pest protection by triggering an RNA interference (RNAi) response or proteins other than Bt Cry proteins. These technologies have new modes of action. Although the overall assessment paradigm for GE plants is robust, there are ongoing discussions about the appropriate tests and measurement endpoints needed to inform non-target arthropod assessment for technologies that have a different mode of action than the Bt Cry proteins. As a result, increasing attention is being paid to the use of sublethal endpoints and their value for environmental risk assessment (ERA). This review focuses on the current status and history of sublethal endpoint use in insect-active GE crops, and evaluates the future use of sublethal endpoints for new and emerging technologies. It builds upon presentations made at the Workshop on Sublethal Endpoints for NTO Testing for Non-Bt GE Crops (Washington DC, USA, 4–5 March 2019), and the discussions of government, academic and industry scientists convened for the purpose of reviewing the progress and status of sublethal endpoint testing in non-target organisms.